(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2021)
This investigative work focuses on the determination of the surgical behavior used according to the FLINT classification in patients with colon trauma. In the city of Guayaquil - Ecuador, this colonic lesion has a high incidence in hospital emergencies, such is the case observed during the rotation of surgery at the Hospital de Especialidades Guayaquil “Dr. Albert Gilbert Pontón”. For this reason, we want to determine the efficacy of the application of the Flint classification as surgical behavior of choice in the recovery of patients who entered the emergency operating room for colon trauma in the years 2017 to 2021 at the Hospital de Especialidades Guayaquil “Dr. Albert Gilbert Pontón”. The work is quantitative, non-experimental design, cross-sectional cohort, and descriptive type. The data collection of this research work was based on the review of medical histories and operative records provided by the Hospital de Especialidades Guayaquil “Dr. Albert Gilbert Pontón” from 2017 to 2021, based on ICD 10 S36.5. Results: abdominal trauma occurs in young adult men in an age range of 18-45 years in 82.6% of the total cases, projectiles by firearm caused trauma of the abdomen in 50% of the total cases. The colon was found injured in 61.96% of patients with abdominal trauma. Primary raffia was used in 50.88% of the total cases. Conclusions: It is concluded that the main cause of trauma of the abdomen is by firearm projectile, and the man is the most affected in an age range of 18-45 years. The main organ injured was the colon, occurring in more than half of the cases. The surgical behavior of choice was primary raffia in grade 1 colon lesions according to the Flint scale.